Micromagnetic and rock magnetic data of sediment core SO240_81-1 from the Clarion-Clipperton Zone, NE Pacific - Adrian Höfken; Tilo von Dobeneck; Thomas Kuhn; Sabine Kasten (PANGAEA, 2024)
The data set presented here comprises high-resolution rock magnetic and micromagnetic data from sediment core 81-SL recovered during RV-Sonne expedition SO240 to the Clarion-Clipperton Zone in the Eastern low latitude North Pacific (Kuhn et al., 2015; doi: 10.2312/cr_so240). The dataset includes the paleomagnetic age model of the core (Höfken et al., 2021; doi: 10.3389/feart.2021.689931). Based on discrete cube samples we prepared high resolution anhysteretic demagnetization and coresponding median destructive field data (ARM, MDFARM). For 39 of the samples, spanning the complete length of the core, first-order-reversal-curve (FORC) measurements are provided. To achieve maximum precision three measurements per sample are included in each dataset. From these FORC measurements we prepared two novel parameters (MUNISD for fine magnetite concentration, Bcmax for fine magnetite stability) that indicate the distribution and degree of preservation of biogenic magnetite in this core. The detailed description of these parameters is published in (Höfken et al., 20XX in preparation). Additionally FORC measurements of an extract of the coarse magnetic fraction of one sample is provided for comparison purpose. With this combined data we investigated the distribution of biogenic magnetite in these sediments as well as magnetofossil preservation.